Rumlig praksis – Konstitution af rum mellem materialitet og repræsentation - Simonsen, Kirsten (Slagmark - Tidsskrift for idéhistorie, 2018)
The purpose of the paper is to outline a conception of space which is basically social and based in an ontology of practice. After a short introduction that ground the paper in the contemporary discussion of a ‘spatial turn’ and in the related discussion within human geography, the purpose is pursued in two steps. First, the social ontology of practice is shortly outlined, and it is discussed how a conception of space starting from that will be. The French philosopher Henri Lefebvre provides a substantive part of the inspiration for that. The second step is to specify operations in work in this space, developed under the notions of embodied spaces and narrative spaces. The paper ends by discussing the relationship between space, time and mobility